S01.5 The architecture for prevention and the role of targets and indicators. (13th September 2015) - Warren, Mitchell
Abstract : There are effective means to prevent every mode of transmission; political commitment on HIV continues to be strong; and financing for HIV programs in low- and middle-income countries increased has surpassed US$17 billion. However, amidst recurring calls for a comprehensive, integrated and sustained AIDS response, funding, targets and delivery are focusing disproportionately on treatment. This presentation will describe the financing, leadership and implementation/delivery architecture for HIV prevention as it exists today, and as it needs to be developed in order to fully realise the potential of existing, emerging and on-the-horizon HIV prevention options. Beginning with an exploration of the current architecture of HIV prevention financing, the presentation will highlighting current gaps, such as the recent scale back of PEPFAR funding for VMMC and shortfalls in funding and planning for PrEP product introduction, citing these examples to highlight broader issues in the architecture as it exists (e.g. the gap between positive research results and substantive, strategic planning to move to implementation), individual interventions (e.g. VMMC) being "owned" by single donors, and then in jeopardy when funding fluctuates. The presentation will also explore the leadership, describing the actors that influence policy, programming and messaging at global, regional and national levels. Finally, this presentation will examine the gaps and strengths in current implementation and delivery architecture, focusing on what is available and/or needed to deliver prevention and on the targets that need to be set to help drive implementation and financing; how targets need to be tailored to each specific intervention; and highlight the potential for conceiving and building a comprehensive prevention delivery platform that maximises the use of existing interventions and supports the rapid and effective integration of new options as they become available.